2014
DOI: 10.4103/1673-5374.135325
|View full text |Cite|
|
Sign up to set email alerts
|

Differential gene expression in proximal and distal nerve segments of rats with sciatic nerve injury during Wallerian degeneration

Abstract: Wallerian degeneration is a subject of major interest in neuroscience. A large number of genes are differentially regulated during the distinct stages of Wallerian degeneration: transcription factor activation, immune response, myelin cell differentiation and dedifferentiation. Although gene expression responses in the distal segment of the sciatic nerve after peripheral nerve injury are known, differences in gene expression between the proximal and distal segments remain unclear. In the present study in rats,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Up-regulated MMP9 stimulates the recruitment and migration of macrophages, mediates the differentiation of myelinating Schwann cells, and thus benefits nerve regeneration (Shubayev et al, 2006; Kim et al, 2012). Our earlier studies also demonstrated that two other members of the MMP family, MMP7 and MMP12, were kept up-regulated following nerve injury (Jiang et al, 2014; Qin et al, 2016). All these results highlight the central roles of the MMP family in nerve regeneration.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Up-regulated MMP9 stimulates the recruitment and migration of macrophages, mediates the differentiation of myelinating Schwann cells, and thus benefits nerve regeneration (Shubayev et al, 2006; Kim et al, 2012). Our earlier studies also demonstrated that two other members of the MMP family, MMP7 and MMP12, were kept up-regulated following nerve injury (Jiang et al, 2014; Qin et al, 2016). All these results highlight the central roles of the MMP family in nerve regeneration.…”
Section: Discussionmentioning
confidence: 77%
“…Certainly, the gene expression patterns and activated biological processes in the distal nerve stump showed different characteristics compared to those in the proximal nerve stump. There has been a previous study which compared the differentially gene expressions in proximal and distal nerves after nerve injury (Jiang et al, 2014). It should be known that the proximal and the distal nerve stumps may share many common genes but have different spatiotemporal expression patterns after nerve injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complex correlations between Schwann cells, macrophages, and axons during nervous demyelinating and myelin regeneration (Jiang, Li, et al, 2014;McLean & Verge, 2016;Niemi et al, 2013). Complex correlations between Schwann cells, macrophages, and axons during nervous demyelinating and myelin regeneration (Jiang, Li, et al, 2014;McLean & Verge, 2016;Niemi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the inflammation plays a key role in a series of pathological reaction of neurological disease. Complex correlations between Schwann cells, macrophages, and axons during nervous demyelinating and myelin regeneration (Jiang, Li, et al, 2014;McLean & Verge, 2016;Niemi et al, 2013). Inflammatory response is a hallmark of demyelinating pathology.…”
Section: Introductionmentioning
confidence: 99%